Implementasi Budaya 5S dalam Membentuk Karakter Anak Usia Dini di RA Muslimat NU Gumawang Pekalongan - FA Sunny; AB Illahi; DH Lestari (Prodi PIAUD IAI Pangeran Dharma Kusuma Indramayu, 2024)
Early childhood education is a very important stage of education to pay attention to together. Through this education, we can form a great next generation with good language skills. The purpose of this writing is to emphasize the importance of the 5S cultural values ​​(Smile, Greetings, Greetings, Politeness and Manners) in elementary school education, in order to shape good student character. The type of research used by researchers is descriptive qualitative, or field research, which relies on data obtained directly from the research location. In this case, researchers conducted research at RA Musliamat NU Gumawang. Qualitative research aims to understand the phenomena experienced by research subjects, such as behavior, perceptions, motivations, actions, and so on. Research results are presented in the form of descriptions using words and language in specific natural contexts, and utilizing various appropriate methods. However, the cultural values ​​that exist in people's lives today are experiencing a decline and are starting to be forgotten along with the times. It can be concluded that implementing good communication skills from an early age is very important. Elementary schools have a significant role in implementing cultural values. Therefore, implementing the 5S culture (Smile, Greeting, Greeting, Polite and Polite) to students from an early age aims to instill habits that can shape students' character well.